2012
DOI: 10.1089/fpd.2011.0991
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Molecular Characterization ofEscherichia coliO157 from Broiler and Human Samples

Abstract: There is a lack of information about the role of poultry, specifically chicken, in transmission of Escherichia coli (E. coli) O157 and subsequent human illnesses. This study was therefore aimed at investigating the presence of E. coli O157 and its virulence genes in various samples collected from broiler chickens and humans in Eastern Turkey by culture, immunomagnetic separation (IMS), and polymerase chain reaction (PCR). The genetic relationship between broiler and human isolates was also examined by pulsed-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
5
5
0
2
Order By: Relevance
“…The isolates were also found as negative to MR test, VP test and positive to indole, catalase and oxidase test, as reported by Buxton and Fraser, (1977). Also in this study, colony characteristics of the isolated E. coli observed on NA, EMB and MacConkey agar were similar to the findings of Kalin et al, (2012); Nazir et al, (2005). The E. coli isolates revealed a complete fermentation of 5 basic sugars by producing both acid and gas which was supported by Thomas et al, (1998).…”
Section: Resultssupporting
confidence: 90%
“…The isolates were also found as negative to MR test, VP test and positive to indole, catalase and oxidase test, as reported by Buxton and Fraser, (1977). Also in this study, colony characteristics of the isolated E. coli observed on NA, EMB and MacConkey agar were similar to the findings of Kalin et al, (2012); Nazir et al, (2005). The E. coli isolates revealed a complete fermentation of 5 basic sugars by producing both acid and gas which was supported by Thomas et al, (1998).…”
Section: Resultssupporting
confidence: 90%
“…In contrast to our findings, some positive results of isolation of E. coli O157:H7 have been reported by other researchers in poultry and other avian species. Kalin et al, (2012) had a 0.1% and 0.4% isolation of E. coli O157:H7 from liver and caecum samples respectively of 1000 chickens investigated in Turkey. All the isolates were positive for eaeA gene; a virulence factor responsible for human infections (Wang et al, 2002).…”
Section: Table Iii: Distribution Of Non-sorbitol Fermenting Escherichmentioning
confidence: 97%
“…Ruminants especially cattle have been established as major reservoir of E. coli O157:H7 (Witold and Carolyn, 2011). In addition, some earlier studies (Dipineto et al, 2006;Kalin et al, 2012) reported isolation of E. coli O157:H7 in living layer hens and post mortem samples of broiler liver and caecum and from contaminated poultry meat and faeces (Olatoye et al, 2012;Aibinu et al, 2007). Some of the isolates from the aforementioned studies possessed hlyA (enterohaemolysin) and eaeA (intimin) genes which are known virulence factors of human pathogenic strains; bringing to the fore public health concerns of cross transmission (Wang et al, 2002;Rwego et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Raw or undercooked meats may pose the agent. Although E. coli O157 has been found in animals such as cattle, sheep, pigs, and goats, studies indicated that poultry may also carry it and pose health risk to humans [11] .…”
Section: Discussionmentioning
confidence: 99%